Impact of the Covid-19 Pandemic on Indonesian Migrant Workers of West Kalimantan - Astono, Agustinus; Dawi, Klara; Yuliastini, Anita; Arabiyah, Syarifah; Christina Sitorus, Angelia Pratiwi Mastiurlani (KnE Social Sciences, 2023)
COVID-19 has had a significant impact on various aspects of life, particularly on Indonesian migrant workers (IMWs). In the early months of 2020, 100,094 IMWs from 83 countries returned to Indonesia due to the spread of COVID-19. This unexpected return was a consequence of the pandemic’s effects on the global economy, leading to layoffs of international workers, including IMWs. During the COVID-19 outbreak, the government took measures to accommodate the return of Indonesian migrant workers to their home country. This reflects the government’s efforts to improve the governance of IMWs, especially in West Kalimantan, which serves as a transit location for IMWs returning from overseas. The research conducted is sociological jurisprudence research, utilizing both primary and secondary data sources. Primary data sources include observations, interviews, surveys, and questionnaires involving respondents. The research approach aims to describe and provide an overview of the subject under study, with a focus on the challenges faced during the research period. Secondary data sources consist of books, legislation, rules, documents, and other writings related to the topic. According to the study, the COVID-19 pandemic resulted in deportations, repatriations, and other effects on Indonesian migrant workers, especially those from West Kalimantan. In response, the Indonesian government has played both a normative and empirical role in protecting the rights of Indonesian migrant workers, with their welfare being the ultimate goal. Keywords: migrant workers, the impact of the COVID-19 pandemic, legal protection